Learning Strategy to Develop Critical Thinking, Creativity, and Problem-Solving Skills for Vocational School Students - Samani, Muchlas; Sunwinarti, Sunwinarti; Putra, Bima A.W.; Rahmadian, Reza; Rohman, Juni Noor (Jurnal Pendidikan Teknologi dan Kejuruan, 2019)
Critical thinking, creativity, and problem-solving skills are critical for vocational schools graduates to enter the workforce in the industrial era 4.0. This study aims to find a learning strategy that can develop these three skills. The study was carried out at SMK X Mojokerto in the Automotive Technology Program in the academic year of 2017/2018. Data were collected using an observation sheet validated by three experts and tested with inter-rater reliability. The data analysis method is t-test. The results of data analysis showed that the Contextual Project Based Learning (CPjBL) was generally effective to improve critical thinking, creativity, and problem-solving skills. Detailed observation included each of these aspects. The findings showed that the implementation of contextualized learning problems could improve the aspect of originality and problem understanding skills, which was usually difficult to improve. On the other hand, CPjBL was not effective in developing the ability of analysis in critical thinking and look-back in problem-solving skills.